Does Human Capital Contribute to Achieving Economic Growth Path in Pakistan? An Empirical Investigation - Shah, Salyha Zulfiqar Ali; Shabbir, Mah Rukh; Parveen, Sabiha (iRASD Journal of Management, 2022)
This paper tries to investigate the contribution of human capital to economic growth in Pakistan. For this purpose, the education enrollment index has been constructed, as a proxy for human capital. The study has collected secondary time series data and utilized the ARDL technique for the empirical results, during the year 1974-2020. The findings of the study concluded that the education enrollment index show a positive relationship with economic growth. The rate of inflation shows a negative relationship with the GDP growth rate. The results of the study suggested that the provision of education facilities is crucial especially at the higher and secondary levels to pursue the path of economic growth in Pakistan.